Lip Prints – An Identification Aid - Karki, RK (Kathmandu University Medical Journal, 2013)
Background Lip prints are the normal lines and furrows in the form of wrinkles and grooves present in the human lip between the inner labial mucosa and outer skin having certain individual characteristics like fingerprints. Objective The aim of the study was to highlight the importance of lip prints in sex determination related to forensic investigation for identification. Methods Study was conducted on 150 medical students which include 75 males and 75 females of Kathmandu University School of Medical Sciences, Dhulikhel, Kavre on 2011. Lip prints were collected and analyzed as per Suzuki’s classification. Results There was significant difference between male and female lip print patterns. Type II was most common combining both. Type I and I’ was more common in male where as Type I was rare in female. Type II in fourth quadrant was seen in almost all female and also the commonest. Similar patterns in all four quadrants were common findings in female. Conclusion The study showed that each lip print is unique and the sex of the person can be predicted on the basis of patterns present in prints. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 55-57 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7345